DEVELOPMENT OF METHODS TO REDUCE THE BENDING OF SHAFTS AND STUDY THE TECHNOLOGY OF THEIR PROCESSING (Conference Zone, 2022)
In the article, the task of reducing the mass of the main working body of the gin, i.e. the cylinder shaft by means of the opening of the groove and the design features of the shaft is determined.Its essence is that the inner groove part of the gin saw cylinder shaft performs the circular side with symmetrical gearsand the entry of external slits into the grooves in the corresponding inner slits of the shaftleads to a specific equilibrium of the mass relative to the axis of rotation and increases its strength and reliability in operation. This will increase resource efficiency and reliability by significantly reducing the mass of the shaft and saw cylinders without significantly reducing the bending stiffness, as well as obtaining cotton fiber with the required quality characteristics. The issues of creating and defining methods for calculating high-efficiency machine drives and shafts are especially important in the creation of machines for the ginning industry